Effects of Medium Characteristics on Laser RCS of Airplane with E-Wave Polarization. (10th November 2015) - El-Ocla, Hosam
Abstract : Plane wave incidence should be postulated to have an authentic target detection. Practically, the plane wave is incapable usually of keeping its power in the far field especially when propagating through an inhomogeneous medium. Consequently, we assume an incident beam wave with a finite width around the target. In this work, we calculate numerically a laser radar cross section (LRCS) of conducting targets having smooth cross sections with inflection points such as airplane in random media. Effects of fluctuations intensity of random media on the LRCS performance are studied in this paper. E-wave polarization (E-wave incidence) is considered while the mean target size is approximately twice the wavelength.